HUBUNGAN KARAKTERISTIK IBU HAMIL TERHADAP PERILAKU PENCEGAHAN STUNTING - Jumiati Jumjum (Poltekkes 'Aisyiyah Banten, 2022)
Background: Prevention of stunting starting from the beginning of pregnancy must be done in order to reduce the incidence of stunting in children. Incidence of stunting can occur during pregnancy due to inadequate nutritional intake during pregnancy, inappropriate eating patterns, and low food quality resulting in stunted growth. Objective: The study was to determine the relationship between the characteristics of pregnant women in preventing stunting at the Serang City Health Center. Design This research is cross-sectional. The research population was pregnant women in the second trimester in the working area of ​​the Mapane Health Center, totaling 49 people. The sampling technique used is total sampling. Methods: research with a cross sectional approach with a sample of pregnant women with anemia or KEK at the Serang City Health Center by testing specific hypotheses to find out whether the relationship or significant effect between the research variables has implications for stunting prevention. Conclusion: There is a significant relationship between the work of pregnant women who experience anemia and stunting prevention behavior at Serang City Health Center in 2022. There is no significant relationship between Age, Gravida and Education of pregnant women who experience anemia with stunting prevention behavior at Serang City Health Center in 2022 Suggestion: midwives in providing counseling or counseling to pregnant women are always accompanied by families who are at home or close to where they live so that they can remind each other if there are habits or lack of nutrition for the health of pregnant women and the growth and development of their babies.